Adverse events of special interest in clinical trials of rheumatoid arthritis, psoriatic arthritis, ulcerative colitis and psoriasis with 37 066 patient-years of tofacitinib exposure. Issue 2 (27th May 2021) - Burmester, Gerd R; Nash, Peter; Sands, Bruce E; Papp, Kim; Stockert, Lori; Jones, Thomas V; Tan, Huaming; Madsen, Ann; Valdez, Hernan; Cohen, Stanley B
Abstract : Objectives: To analyse adverse events (AEs) of special interest across tofacitinib clinical programmes in rheumatoid arthritis (RA), psoriatic arthritis (PsA), ulcerative colitis (UC) and psoriasis (PsO), and to determine whether the incidence rates (IRs; unique patients with events per 100 patient-years) of these events are consistent across diseases. Methods: The analysis included data from patients exposed to ≥1 dose of tofacitinib in phase 1, 2, 3 or 3b/4 clinical trials and long-term extension (LTE) studies (38 trials) in RA (23 trials), PsA (3 trials), UC (5 trials) and PsO (7 trials). All studies were completed by or before July 2019, except for one ongoing UC LTE study (data cut-off May 2019). IRs were obtained for AEs of special interest. Results: 13 567 patients were included in the analysis (RA: n=7964; PsA: n=783; UC: n=1157; PsO: n=3663), representing 37 066 patient-years of exposure. Maximum duration of exposure was 10.5 years (RA). AEs within the 'infections and infestations' System Organ Class were the most common in all diseases. Among AEs of special interest, IRs were highest for herpes zoster (non-serious and serious; 3.6, 1.8, 3.5 and 2.4 for RA, PsA, UC and PsO, respectively) and serious infections (2.5, 1.2, 1.7 and 1.3 for RA, PsA, UC and PsO, respectively). Age-adjusted and sex-adjusted mortality ratios (weighted for country) were ≤0.2 across cohorts. Conclusions: The tofacitinib safety profile in this analysis was generally consistent across diseases and with longer term follow-up compared with previous analyses.